Christian values in education: teachers in India narrate the impact of their faith and values on practice. Issue 3 (2nd July 2020) - Elton-Chalcraft, Sally; Cammack, Paul J.
ABSTRACT: India's education system is complex because it has to meet the needs of a population which is culturally, geographically, politically, religiously and economically diverse. The principal investigator spent two summers in India talking with teachers and learners. This paper reports on the impact of Christian values in the secular but arguably Hindu nationalist education system. Working within an interpretivist paradigm and through an ethnographic lens, an interpretive phenomenological analysis approach was adopted to make sense of 34 interviewees' narratives from five Indian states. The narratives were mapped onto an adaptation of a 'tree metaphor' to illustrate how values underpin decision-making and action in the school context. Five of the narratives are presented as keyhole examples to exemplify the similarities and contrasts in reported beliefs, values and behaviours set within the context of teachers' professional practice. Findings reveal that all 34 participants drew on their Christian faith, and Indian cultural context, in their decision-making both in how they made sense of education policy, and how they interpreted school events and behaviours. Despite their common faith (Christianity), the 34 interpretations, decision-making and actions varied as demonstrated in the five selected narratives. We explore how the variance manifested and was influenced by the geographical, cultural, post colonial and school context.